USING AUDIO VISUAL MEDIA IN TEACHING AND LEARNING ENGLISH TO IMPROVEVOCABULARY OF THE SEVENTH GRADE STUDENT OF SMP NEGERI 2 EAST ROTE - Dopena, Heni Luisa Sarlince; Bera, Laurensius Kian; Taka, Soleman Dapa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to describe the improvement of students' vocabulary using audio-visual media. This research is a Classroom Action Research conducted in 1 cycle, consisting of 4 stages: planning, action, observation, and reflection. With 21 students, the research findings show that in the post-test, only 7 students (33%) achieved the KKM score (75), while 10 students (48%) were below and 4 students got average grades KKM. In the pre-test, only 4 students (19%) did not achieve the KKM score, while 17 students (81%) exceeded the KKM score. The description of learning outcomes using audio-visual media shows that 81% of students are in the complete category, and only a few students did not pass in the pre-test (19%). However, in the post-test, 33% of students did not pass. This illustrates that learning with audio-visual media has been going well and can support the improvement of vocabulary from the learning outcomes of audio-visual media. Therefore, it is recommended that teachers prioritize the use of audio-visual media in teaching subjects.